Ultrasonic cavity preparation using CVD coated diamond bur: A case report - Vasconcellos, Beatriz Tholt de; Thompson, Jeffrey Y; Paula Macedo, Manoel Roberto de; Oliveira Maia, Janaína Monalisa de Oliveira; Oda, Margareth; Netto, Narciso Garone (European Journal of Dentistry, 2013)
Before any restorative procedure can be undertaken a proper cavity preparation is required. This clinical step is the mechanical alteration of the tooth to receive a restorative material with which a satisfactory form, function and the esthetics of the tooth will be established. In recent years improvements in materials and techniques have been devised and new technologies are now available for this purpose. The aim of the present study is to report two clinical cases in which a CVD coated diamond bur coupled to an ultrasonic handpiece is used in dental preparation. This technique provides an accurate and conservative tooth preparation with ideal access and visibility and because of enhanced efficiency can also play a role in eliminating some of the patient discomfort of the dental treatment. (Eur J Dent 2013;7:127-132)
Keywords: Dental cavity preparation; ultrasonics; smear layer; CVD bur